Clinical and anthropological profile of children presenting with features of congenital heart disease at tertiary care centre - Doshi, Mili; Jain, Hemant; Saini, Aashish (International Journal of Contemporary Pediatrics, 2022)
Background: Congenital heart diseases (CHD) are one of the most common causes of morbidity and mortality and also contribute to significant amount of malnutrition in pediatric population. This study was conducted to know the clinical features and anthropological parameters in children with CHD. Methods: Children between the age group of 0-18 years with presenting complaints of CHD were enrolled. All relevant information of individual patient were collected. Detailed evaluation and physical examination along with detailed anthropometry measurements were taken. Echocardiograms were performed for definite diagnosis. Results: A total of 70 children were present during the study period. The most common age group for CHD was 1 month to 5 years with 66% (46 cases). Acyanotic heart diseases were observed in 72.9% of cases and cyanotic CHD was observed in 21.4% of cases. VSD was the most common acyanotic CHD with 41.1% cases while TOF was the most common cyanotic CHD with 67% cases. The most usual presenting symptoms in children with CHDs were breathlessness with 70% cases, failure to thrive in 57% cases and cough in 43% cases. Male-to-female ratio was 1.7:1. The 63% children had weight-for-age of ≤3 SD while 61% children had height-for-age of ≤3 SD. Conclusions: Cyanotic CHDs were less common than acyanotic CHDs with infancy and early childhood being the most common age-groups for presentation. Malnutrition is common in children with CHD. Both height and weight were affected more in cyanotic group when compared to acyanotic group.